Comparing the Effectiveness of Art Therapy and Cognitive Behavioral Play Therapy on Anxiety and Assertiveness in Preschool Children - Emami Mehr, Sudabeh; Amiri Majd, Mojtaba; Ghamari, Mohammad; Bazzazian, Saeideh (KMAN Counseling & Psychology Nexus, 2026)
Anxiety and assertiveness issues are among the most important challenges among preschool children. This study examines the effectiveness of art therapy and cognitive-behavioral play therapy in reducing anxiety and improving assertiveness in preschool children. The study employed a quasi-experimental pretest-posttest design with a control group. The statistical population included all 5–6-year-old children referred to the Nedaye Aramesh Ravan Counseling Clinic in Tehran. Using Cochran’s formula, 45 eligible children were selected and randomly assigned to two experimental groups and one control group (n = 15 per group). The first experimental group received 10 weekly sessions of art therapy, and the second received 12 weekly sessions of cognitive-behavioral play therapy. The control group did not receive any intervention during the study period. Data were collected using the Preschool Anxiety Scale (PAS) and the Social Skills Rating System (SSRS). Data analysis was performed using multivariate analysis of covariance (MANCOVA) in SPSS-23. Both art therapy and cognitive-behavioral play therapy led to significant reductions in anxiety and increases in assertiveness compared with the control group after the intervention (P < 0.001). However, the difference in effectiveness between the two therapeutic approaches was not statistically significant (P > 0.05). Both art therapy and cognitive-behavioral play therapy were effective in reducing anxiety and enhancing assertiveness in preschool children. Although each approach relies on different therapeutic mechanisms, their outcomes were comparable, indicating similar therapeutic value. These findings suggest that either intervention can be appropriately selected based on the child’s needs and treatment context.